Treatment of Inflammatory Bowel Disease by Using Curcumin-Containing Self-Microemulsifying Delivery System: Macroscopic and Microscopic Analysis - Nabeela Ameer; Muhammad Hanif; Ghulam Abbas; Muhammad Azeem; Khalid Mahmood; Dure Shahwar; Ahmed Khames; Essam Mohamed Eissa; Baher Daihom (Pharmaceutics, 2024)
Background: The lack of local availability for drugs in the colon can be addressed by preparing a self-microemulsifying drug delivery system (SMEDDS) of curcumin (Cur) which is ultimately used for the treatment of inflammatory bowel disease (IBD). Methods: From preformulation studies, Lauroglycol FCC (oil), Tween 80 (surfactant), Transcutol HP (co-surfactant), and Avicel (solid carrier) were selected for the preparation of blank liquid and solid Cur-loaded SMEDDSs (S-Cur-SMEDDSs). Results: Z-average size (12.36 ± 0.04 nm), zeta potential (−14.7 ± 0.08 mV), and polydispersity index (PDI) (0.155 ± 0.036) showed a comparative droplet surface area and charge of both SMEDDSs. The physicochemical stability of Cur in S-Cur-SMEDDSs was confirmed via FTIR, DSC, TGA, and XRD analyses, while morphological analysis through SEM and atomic force microscopy (AFM) confirmed Cur loading into SMEDDSs with an increased surface roughness root mean square (RMS) of 11.433 ± 0.91 nm, greater than the blank SMEDDS. Acute toxicity studies with an organ weight ratio and % hemolysis of 15.65 ± 1.32% at a high concentration of 600 mM showed that S-Cur-SMEDDSs are safe at a medium dose (0.2–0.8 g/kg/day). The excellent in vitro antioxidant (68.54 ± 1.42%) and anti-inflammatory properties (56.47 ± 1.17%) of S-Cur-SMEDDS proved its therapeutic efficacy for IBD. Finally, S-Cur-SMEDDS significantly improved acetic acid-induced IBD in albino rats through a reduction in the disease activity index (DAI) and macroscopic ulcer score (MUS) from 4.15 ± 0.21 to 1.62 ± 0.12 at 15 mg/kg/day dose, as confirmed via histopathological assay. Conclusions: Based on the above findings, S-Cur-SMEDDS appears to be a stable, less toxic, and more efficacious alternative for Cur delivery with strong competence in treating IBD.